Polycyclic aromatic hydrocarbons in soils of the central Tibetan Plateau, China: Distribution, sources, transport and contribution in global cycling. (August 2015) - Yuan, Guo-Li; Wu, Li-Juan; Sun, Yong; Li, Jun; Li, Jing-Chao; Wang, Gen-Hou
Abstract: Forty-four soil samples were collected across the central Tibetan Plateau (CTP) at altitudes between 3711 m and 5352 m, and their polycyclic aromatic hydrocarbons (PAHs) contents were measured to be from 0.43 to 26.66 ng/g. The main sources of PAHs were identified for each of four sub-areas, and their concentrations in soils were determined to be mainly influenced by local sources. Along a 600 km sampling trajectory from Lhasa, which served as the biggest local source, the concentrations of PAHs decreased logarithmically with increasing distances from the source. Meanwhile, the fractional proportions of PAHs were observed to change logarithmically according to the transport distances. Conclusively, PAHs from local sources were transported within the CTP and dominated PAHs concentrations in the soils, but few of them were transported outside the CTP. In global cycling, the soils in the CTP mainly serve as background and a "sink" for PAHs. Graphical abstract: Highlights: Main sources of PAHs were identified for each of four sub-areas in CTP. Local sources dominated PAHs in soils but rarely transported outside CTP. The PAHs in soils changed logarithmically according to the distances from source. It is first revealed how the local PAH sources influenced PAHs in the soils of CTP. Abstract : Local sources dominated PAHs concentrations in the soils of CTP but rarely transported outside, and PAHs in soils changed logarithmically according to the transported distances.